Real Interest Rate Targeting : An Example From Brazil - Clifton, Eric (IMF Working Papers; Working Paper, 1990)
This paper examines a real interest rate targeting procedure based on lagged inflation similar to the policy followed by the Brazilian monetary authorities during the period November 1986 to December 1988, focusing on the issue of the determinacy of the price level. For the specific model examined, the analysis suggests that such a targeting procedure would not suffer from the frequently noted defect of nominal interest rate targeting rules of leaving the conditional expectation of the next period price level undetermined.